2011
DOI: 10.1055/s-0030-1269847
|View full text |Cite
|
Sign up to set email alerts
|

Direct Costs of Diabetes Mellitus in Germany – CoDiM 2000–2007

Abstract: There was a continuous increase in the prevalence of diabetes in Germany during the 8-year period. Although there was only a modest increase in annual diabetes-related per-capita costs, total healthcare expenditure rose substantially due to the growing number of patients being treated for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 7 publications
9
70
0
7
Order By: Relevance
“…Productivity losses due to morbidity and mortality, which are a part of the indirect costs, were included only for deaths occurring among adults of working age (<65 y old). For the CoI analysis related to diabetes (SI Appendix, section SI.4), we adopted country-specific cost estimates (48) and, to avoid double-counting of cardio vascular disease-related complications, adjusted those estimates for the incremental cost component specifically attributable to diabetes (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Productivity losses due to morbidity and mortality, which are a part of the indirect costs, were included only for deaths occurring among adults of working age (<65 y old). For the CoI analysis related to diabetes (SI Appendix, section SI.4), we adopted country-specific cost estimates (48) and, to avoid double-counting of cardio vascular disease-related complications, adjusted those estimates for the incremental cost component specifically attributable to diabetes (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…According to the German data of myocardial infarctions, [50][51][52] Costs for myocardial infarction in Germany, as assessed by the German epidemiological CoDiM Study, 20,53,54 were calculated to be €9767 per myocardial infarction and €4032 for costs related to the first year of follow-up after an acute myocardial infarction. Adding the two parameters of costs for myocardial infarction, €13,799 per successfully treated myocardial infarction were incorporated into the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the German health care system, this may add up to annual savings of €9.4 million in type 1 diabetes patients and €55.5 million in the entire group of insulintreated patients. In light of annual diabetes-related costs in Germany of €19.1 billion, 20 the savings are considered to be a substantial contribution to reducing costs in the health care system of Germany. Data of an in silico analysis were included in our analysis, 17 which demonstrated that a higher accuracy may translate into a 10% reduction of severe hypoglycemic events and a mean HbA1c reduction of 0.39%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 10 years, the incidence of T1DM increased on average by 2.5-3 % per year worldwide [19] and so is for the number of patients treated with insulin or insulin plus oral antidiabetic agents [11,20], and frequency of hypoglycemia is also raising [21].…”
Section: Introductionmentioning
confidence: 99%